Ответ:
-(3 + 2b)/(3 - 2b)
Пошаговое объяснение:
((3 - (9 + 4b²)/(3 + 2b)) * ((1/2b + 2/(3 - 2b)) =
((3 - (3 + 2b)*(3 + 2b)/(3 + 2b)) * ((3 - 2b + 4b)/2b*(3 - 2b)) =
((3 - (3 + 2b)) * ((3 + 2b)/2b*(3 - 2b)) =
(3 - 3 - 2b) * ((3 + 2b)/2b*(3 - 2b)) =
-2b * ((3 + 2b)/2b*(3 - 2b)) = -(3 + 2b)/(3 - 2b)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
-(3 + 2b)/(3 - 2b)
Пошаговое объяснение:
((3 - (9 + 4b²)/(3 + 2b)) * ((1/2b + 2/(3 - 2b)) =
((3 - (3 + 2b)*(3 + 2b)/(3 + 2b)) * ((3 - 2b + 4b)/2b*(3 - 2b)) =
((3 - (3 + 2b)) * ((3 + 2b)/2b*(3 - 2b)) =
(3 - 3 - 2b) * ((3 + 2b)/2b*(3 - 2b)) =
-2b * ((3 + 2b)/2b*(3 - 2b)) = -(3 + 2b)/(3 - 2b)